2013
DOI: 10.5194/bg-10-1737-2013
|View full text |Cite
|
Sign up to set email alerts
|

Root growth of <i>Lotus corniculatus</i> interacts with P distribution in young sandy soil

Abstract: Abstract. Large areas of land are restored with unweathered soil substrates following mining activities in eastern Germany and elsewhere. In the initial stages of colonization of such land by vegetation, plant roots may become key agents in generating soil formation patterns by introducing gradients in chemical and physical soil properties. On the other hand, such patterns may be influenced by root growth responses to pre-existing substrate heterogeneities. In particular, the roots of many plants were found to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The lack of a P fertilization effect on shoot biomass production was in contrast to P-limited growth observed on the same soil in Lotus corniculatus L. (Felderer et al 2013). It may have been due to a higher P acquisition efficiency of white lupin and/or to a larger P supply from the seeds.…”
Section: Effects Of Water and P On Shoot Root And Cluster Root Growthmentioning
confidence: 58%
“…The lack of a P fertilization effect on shoot biomass production was in contrast to P-limited growth observed on the same soil in Lotus corniculatus L. (Felderer et al 2013). It may have been due to a higher P acquisition efficiency of white lupin and/or to a larger P supply from the seeds.…”
Section: Effects Of Water and P On Shoot Root And Cluster Root Growthmentioning
confidence: 58%
“…The mentioned Chicken Creek project led to a number of results that are of importance for the understanding of initial ecosystem state transitions (see Hüttl et al, 2013): It was found that the basic assumption of low heterogeneity and structuring of ecosystems in their initial stage was essentially correct. Though small, it seems that these heterogeneities were of great importance for the later development of the system, however, as highlighted by Felderer et al (2013) and Biber et al (2013) in this issue. This relates to earlier publications from the Chicken Creek project, which show that slight differences in substrate properties influenced hydrological pathways, such as erosion rill patterns (Hofer et al, 2012) and groundwater flow patterns (Hofer et al, 2011).…”
Section: Central Findings From Initial Ecosystem Researchmentioning
confidence: 80%
“…Fischer et al (2012) show that biocrusts developing on bare surfaces of initial soils can have direct feedbacks effects on physical site conditions. Biber et al (2013) analyze relationships between initial site conditions and evolving vegetation patterns, whilst Felderer et al (2013) investigate strategies of plants to forage for phosphorus as a soil nutrient that is often of very low availability in initial ecosystems. Finally, Mueller-Dombois and Boehmer (2013) summarize the long-term primary succession of Hawaiian rainforest ecosystems which may serve as reference sites for initial ecosystems due to frequent disturbances by volcanism.…”
Section: This Special Issue -Case Studies Of Initial Ecosystemsmentioning
confidence: 99%
“…Favorable effects on root development of L. corniculatus were observed in sandy soils containing finer-textured fragments (Boldt-Burisch et al 2013). As nutrient availability is usually limited under initial soil conditions and particularly phosphorus is a limiting factor for plant growth, it was observed both under experimental and field conditions that L. corniculatus roots increase and are preferentially abundant in P-enriched soil patches (Felderer et al 2013). Due to P uptake by roots and mycorrhizal fungi a depletion of P in these patches revealed that the original distribution of nutrients is changed by the developing vegetation.…”
Section: Ecosystem Development After Miningmentioning
confidence: 99%